Conservative vs Surgical Treatment of Impacted Femoral Neck Fracture in Patients 75 Years and Older. Issue 10 (15th May 2020) - Wei, Peiran; Xu, Yan; Gu, Yue; Geng, Dawei; Yao, Qingqiang; Wang, Liming
Abstract : OBJECTIVE: To evaluate the safety and effectiveness of conservative treatment (CST), internal fixation (IF), and hemiarthroplasty (HA) in treating patients older than 75 years with impacted femoral neck fracture (IFNF). DESIGN: A randomized clinical trial to compare clinical outcomes of CST, IF, and HA in IFNF patients older than 75 years with a 1:1:1 ratio. SETTING: Nanjing First Hospital, Nanjing Medical University, Nanjing, China. PARTICIPANTS: A total of 154 patients with IFNF aged between 75 and 97 years. INTERVENTION: Patients with IFNF were allocated to CST, IF, and HA. They all received a 36‐month follow‐up. MEASUREMENTS: All patients were evaluated by Harris hip score (HHS) (primary outcome) for hip function, European Quality of Life‐5 Dimensions (EQ‐5D) index scores for health‐related quality of life, and visual analogue scale score for hip pain. Operation duration, blood loss, mortality, union rate, complications, and reoperation were also recorded. Assessors were blind to the type of treatment. RESULTS: The baseline parameters of the three groups were similar. IF group had much lower blood loss than HA group ( P  < .05), while no significant difference in operative duration was found between the two groups ( P  > .05). HHS in HA group was significantly higher at 1, 3, and 6 months ( P  < .05), but no significant difference in HHS was found between CST and IF groups at any of the time points during the overall follow‐up ( P  > .05). EQ‐5D index score was higher in HA group at each follow‐up within 1 year ( P  < .05), but the difference was not significant at 2‐ and 3‐year follow‐up ( P  > .05). There was no significant difference in mortality among the three groups at each follow‐up point ( P  > .05). The nonunion rate was 11.76% (6/51) in CST group and 9.80% (5/51) in IF group and showed no significant difference ( P  > .05). CONCLUSION: CST may be a feasible way for IFNF in the older patients. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04219943. J Am Geriatr Soc 68:2214–2221, 2020.